KEEFEKTIFAN PERMAINAN “FIND THE DIFFERENCE” TERHADAP KEMAMPUAN BEBRBICARA SISWA TAHUN KEDUA SMP BABUSSALAM PEKANBARU - Delviana Anggra Mustikah; Atni Prawati; Hadriana ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This pre-experimental research aimed to know the effectiveness of “find the difference” game on speaking ability of the second year students of SMP Babussalam Pekanbaru. This research was conducted toward the second year students of SMP Babussalam Pekanbaru from October to November 2015. The researcher used cluster random sampling technique to determine the sample. The sample was class VIII.4 which consisted of 23 students. The data was collected by giving a pre-test and a post-test to students in the form of picture describing. The data was assessed by three raters and analyzed by using SPSS 18. The result of the reserch showed the different score in the pre-test and the post-test was 27.42. The score of the pre-test was 45.62 and the score of the post test increased to 73.04. Moreover, from statistical analysis, it was found out that the t-test 23.320 was bigger than t-table 2.074 at level significance of 0.05. It means that there was a significant effect of “Find the Difference” game on the students’ speaking ability. Therefore, it can be concluded that applying “Find the Difference” game is effective to improve students’ speaking ability.Keywords:”Find the Difference” game, Speaking Ability